Construction of an evaluation index system for teacher education students’ information literacy: an empirical analysis of Chinese postgraduate programs - Shi Chen; Sabariah Mohamed Salleh; Mohd Azul Mohamad Salleh; Fei Zhou (Humanities & Social Sciences Communications)
Abstract Postgraduates play a central role in the cultivation of information literacy. It is of great significance to construct an evaluation index system for their information literacy based on the characteristics of different disciplines. This study evaluates the information literacy of Chinese teaching postgraduates using the Delphi method, analytic hierarchy process (AHP), questionnaires, and fuzzy comprehensive evaluation method. Based on two rounds of the Delphi method, an evaluation index system was developed, consisting of four primary indexes, 14 secondary indexes, and 38 tertiary indexes. AHP was used to calculate the weights of each index, with consistency checks completed. The primary indices, in order of importance, were ranked as follows: information behavior and innovation > information knowledge and skills > information security and ethics > information awareness and demand. Among them, information behavior and innovation are the focus of students’ information literacy development. Empirical analysis revealed that the overall information literacy level of Chinese teaching postgraduates was good. The levels of information awareness and demand, as well as information security and ethics, were excellent, while information knowledge and skills, alongside information behavior and innovation, were rated as good.